Microstructure Behavior of Batu Pahat Soft Clay (BPSC) Stabilized with Sodium Silicate (TX-85) And Biomass Silica (SH-85) - Hassan, Muhammad Hairi; Ahmad Tajudin, Saiful Azhar; Mat Nor, Ahmad Hakimi (Recent Trends in Civil Engineering and Built Environment, 2023)
The soft clay soil usually causes problems to civil engineers due to its characters which are low shear strength and high compressibility, and many are sensitive in that their strength is reduced by disturbances. Strengthening and improving the soft clay soil is crucial before any construction work is done by improving the soft ground improvement. This research uses non-traditional chemical stabilization method by combining a fixed percentage (3%) of Sodium Silicate (TX-85) to varying percentage (6%, 9%, and 12%) of Biomass Silica (SH-85) then the samples were cured for (7, 14 and 28 days). The microstructural and mineralogy changes of the sample was observed using X-Ray Diffraction (XRD), and Scanning Electrons Microscopic (SEM) analysis. The results of all tests conducted showed changes in the microstructure behavior of soft clay soil stabilized with Sodium Silicate (TX-85) and Biomass Silica (SH-85). Thus, the XRD the results of the study indicated the presence of a new mineral composition but at a low intensity, as well as an increase in the amount of Quartz mineral due to the addition of stabilizer. Additionally, the void was filled with a stabilizing substance during SEM testing. Additionally, cementation product was detected via the SEM test as a result of the stabilizer given to treated samples. Additionally, the EDX test established that the appearance of the Calcium (Ca) element in the treated sample is a result of the stabilizer’s chemical capabilities. As a result of this research, the relationship between the microstructure and mechanical properties of treated soil may be established.